7 - La Croyance Burundaise Identifiée Après Quarante ans D’Hésitation: Gertrude Ndayipfukamiye - Gertrude Ndayipfukamiye, (African Sociological Review, 2021)
The monotheism that has characterized the Burundian people from time immemorial has long been the subject of controversy in political circles. These hesitations are justified on the one hand by the absence of research on the customary law of religions and, on the other hand, by the clause in the Kiganda Treaty which, by forcing the king to «no longer disturb civilizing action of the Christian mission of Mugera ” reminded us of an attachment of the Burundians to the cults of the ancestors. This study proves that ancestor cults are not the identity religions of Burundians and are in opposition to their true beliefs as well as to the morality of the country. The identity religions of the Burundians are increasing gaining the upper hand while the cults of the ancestors tend to disappear.